The validity and structure of culture-level personality scores : data from ratings of young adolescents - McCrae, Robert R. (Array, 2010)
We examined properties of culture-level personality traits in ratings of targets (N = 5, 109) aged 12 to 17 in 24 cultures. Aggregate scores were generalizable across gender and age groups and showed convergence with culture-level scores from previous studies of self-reports and observer ratings of adults, but they were unrelated to national character stereotypes. Trait profiles also showed cross-study agreement within most cultures, eight of which had not previously been studied. Multidimensional scaling showed that Western and non-Western cultures clustered along a dimension related to Extraversion. A culture-level factor analysis replicated earlier findings of a broad Extraversion factor, but generally resembled the factor structure found in individuals. Continued analysis of aggregate personality scores is warranted.